Effect of grain size on the resistance to hydrogen embrittlement of API 2W Grade 60 steels using in situ slow-strain-rate testing. (November 2017) - Park, Cheolho; Kang, Namhyun; Liu, Stephen
Graphical abstract: Highlights: Hydrogen embrittlement resistance increased with grain size refinement. Quasi cleavage fracture decreased displacement significantly with increasing grain size. The amounts of hydrogen desorbed from lattice sites and grain boundaries increased with decreasing grain size. Fine-grained steel exhibited the lowest normalized hydrogen content in a unit grain boundary. Abstract: This study investigated the grain size effect on the resistance to hydrogen embrittlement (HE) of API 2W Grade 60 steels using in situ slow-strain-rate testing. Hydrogen was electrochemically charged into specimens and the hydrogen content evolved from diffusible hydrogen-trap sites was measured by thermal desorption spectrometry (TDS). The fine-grained (14 μm) steel showed superior HE resistance despite exhibiting higher total hydrogen content than the coarse-grained (35 μm) steel. Decreasing grain size resulted in a larger grain boundary area, thereby better reducing the normalized amount of diffusible hydrogen trapped per unit length of grain boundary.